NORTH CAROLINA’S BLACK PATRIOTS OF THE AMERICAN REVOLUTION - Freeman, W. Trevor (East Carolina University, 2020)
This thesis explores the service of an estimated 468 black men who fought for the American cause during the Revolutionary War. Specifically, it examines those who resided in North Carolina or fought under the forces of this state. While the war largely did not fulfill its egalitarian potential for free and enslaved people of color, the armed service of these men-and their later status as veterans-brought them a mixed array of benefits. This study reveals why these men served, how they affected the war, and how their participation in the military impacted them, their families, and the larger community of people of color within North Carolina. It will show the geographic, economic, and social factors that influenced their enlistment into the Continental and militia forces of the state, as well as the ways their varied service fostered camaraderie and connections with other soldiers. It juxtaposes the ways the war failed veterans "black and white" economically with the tenuous but appreciable social gains made by North Carolina's black veterans: gains that ultimately receded as the living legacy of these soldiers disappeared. Examining these unique soldiers of North Carolina is particularly important as article and even monograph-length treatments of black soldiers in other states exist. This scholarship, specifically focusing on black Patriot soldiers in a Southern state and employing rudimentary quantitative assessments, fills a historiographical void and provides greater understanding of the plight of free people of color within early North Carolina society. Using primarily federal pension applications, troop returns, and rosters of black servicemen in the American Revolution, this thesis attempts to answer these and other questions surrounding North Carolina's black Patriots, and to provide a portrait of their thoughts and actions.
Keywords: United States--History--Revolution, 1775-1783--African Americans; North Carolina--History--Revolution, 1775-1783--Social aspects; African American soldiers--North Carolina--History--18th century